Access to energy services by the poor in India: Current situation and need for alternative strategies - V. S. Ailawadi and Subhes C. Bhattacharyya (Natural Resources Forum 30 (2006) 2-14, 2006)
Poor and inadequate access to clean, reliable and affordable energy is now considered a major concern for sustainable development. India houses about a third of the world's population without access to electricity and about 40